2011
DOI: 10.5344/ajev.2010.10077
|View full text |Cite
|
Sign up to set email alerts
|

Powdery Mildew Severity as a Function of Canopy Density: Associated Impacts on Sunlight Penetration and Spray Coverage

Abstract: Variable canopy densities and associated differences in sunlight distribution within the fruit zones on clusters were quantified and correlated with variable severities of powdery mildew within vineyards in the states of New York, Washington, and South Australia. Canopy density was measured with enhanced point quadrat analysis (EPQA), and the number of shading layers and the photon flux within the fruit zone of individual vines indicated that less disease developed on clusters with more exposure to sunlight. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…"Leaf thinning" from the fruit zone, for example, often entails the combined removal of up to several primary leaves and, with vigorous vines, three or more lateral shoots from the first 10 nodes of the primary shoot. The improved radiation environment and ventilation afforded by these practices reduces bunch rot incidence (Zoecklein et al 1992) and powdery mildew infestation (Austin et al 2011) and is generally considered to improve wine quality potential (Smart et al 1985). In addition to reducing the need for shoot hedging, UTCC, RR, or their combination substantially reduced lateral shoot development within the canopy fruit zone and the need for repeated shoot hedging with VSP-trained canopies.…”
Section: Discussionmentioning
confidence: 99%
“…"Leaf thinning" from the fruit zone, for example, often entails the combined removal of up to several primary leaves and, with vigorous vines, three or more lateral shoots from the first 10 nodes of the primary shoot. The improved radiation environment and ventilation afforded by these practices reduces bunch rot incidence (Zoecklein et al 1992) and powdery mildew infestation (Austin et al 2011) and is generally considered to improve wine quality potential (Smart et al 1985). In addition to reducing the need for shoot hedging, UTCC, RR, or their combination substantially reduced lateral shoot development within the canopy fruit zone and the need for repeated shoot hedging with VSP-trained canopies.…”
Section: Discussionmentioning
confidence: 99%
“…In grapes, leaves are diurnally positioned to avoid excessive photon flux density (Gamon and Pearcy, 1989). Lobing, dissection, and serration in grape leaves are important for light to penetrate the canopy, mitigating not only the establishment of fungal infections (Spotts, 1977;Lalancette et al, 1988;Boso et al, 2010;Austin et al, 2011;Austin and Wilcox, 2012) but influencing cluster development and berry composition (Crippen and Morrison, 1986;Hunter et al, 1991;Morrison and Noble, 1990). Trichome density varies immensely in grape leaves, not only protecting against pathogens but providing photoprotection of the photosynthetic apparatus (Liakopoulos et al, 2006), thermoregulation, and boundary layer maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that different leaf removal methods, including both manual and mechanized, changed the canopy structure, leaf density, and the percentage of leaves and clusters, but did not affect bud fertility, shoot density, nor plant vigor (Percival et al, 1994). Early leaf removal carried out near flowering reduces the supply of carbohydrates to the fruit set/berry development and increases the leaf/fruit and skin/pulp ratios, resulting in less compact clusters which are less susceptible to disease, resulting in improved fruit composition and fewer thinned clusters (Poni et al, 2006;Poni et al, 2008;Poni et al, 2009;Intrieri et al, 2008;Austin et al, 2011). The time of leaf removal and shoot topping may affect fruit composition (Lee and Skinkis, 2013).…”
Section: Introductionmentioning
confidence: 99%